Usefulness of strain imaging to determine prognosis in pulmonary hypertension. (25th November 2020) - Monivas Palomero, V; Remior, P; Garcia-Rodriguez, D; Garcia-Gomez, S; Garcia-Izquierdo, E; Borrego, A; Navarro, S; Martinez Mingo, A; Arellano-Serrano, C; Oteo, J.F; Garcia-Touchard, A; Goicolea, J.F; et al.
Abstract: Introduction: Pulmonary hypertension (PH) is defined as mean pulmonary arterial pressure (mPAP) ≥25 mmHg at rest, measured by right heart catheterization (RHC). Purpose: To describe classical and myocardial deformation echocardiographic parameters in patients with established PH and to identify prognostic variables Methods: We prospectively enrolled 76 patients with mPAP ≥25 mmHg undergoing RHC between 2017 and 2018. All subjects underwent transthoracic echocardiography (TTE) according to the latest ASE/EACVI guidelines the same day of the RHC. Strain analysis was carried out by speckle-tracking echocardiography (QLAB 10.7, Philips). Clinical events during the follow-up were: acute heart failure hospitalization, cardiac transplant and all-cause mortality. Results: Mean age was 59±12, 43.4% were women and 49 patients (64.5%) belonged to group 2 of PH. The median follow-up was 288 (ICR 92–534) days. Total number of events was 42 (55.3%, 9 deaths). Variables associated to events are shown in Table 1. All classic LV and RV systolic function and strain parameters were associated with a worse prognosis, being free-wall RV longitudinal strain (RVLS) the only one that remained as a prognostic factor in mutivariate analysis. Other variables associated with a worse prognosis were PCP>15 mmHg and NT-proBNP>1800, the latter being independent predictor of events. The attached figure shows event-free survival curves for the global population divided according to whether or not they belong to group II PH. Conclusions: Our data highlight the prognostic value of free-wall RVLS and NT-proBNP in patients with established PH. NT-ProBNP was only useful in group II PH while free-wall RVLS identified patients with a higher risk of events in both groups, mainly in patients with heart disease Funding Acknowledgement: Type of funding source: None